Cochliomyia Homnivorax in an advanced stage in the oral cavity - Layla Gomes; Leila Maués Oliveira Hanna; Rodolfo José Gomes de Araújo; Liliane Helena Vilar Carvalho
Myiasis is characterized by the invasion of body or cavity tissues of live animals by larva. It is most frequently observed in underdeveloped and tropical countries, but there are cases described worldwide. Conventional treatment consists of mechanical removal of the larvae, one by one, which is a painful, embarrassing and repugnant process, both for the professional and patient. Although it is not considered rare, it has been observed that the dental professional has little knowledge for the diagnosis and treatment of this pathology. For this reason, this study reports a case of oral myiasis at an advanced stage, which affected a nine-year-old patient, treated at a medical-dental clinic. Diagnosis was based on the visual presence of Cochliomyia homnivorax larvae, diptera of the Calliphoridae family, which were between the second and third stages of development. Predisposing factors, such as the lack of information, malnutrition, poor oral hygiene, preexistenceof oral lesions and severe halitosis have a decisive influence in the appearance and progression of oral myiasis. A brief literaturereview was also conducted, in which this pathology was discussed, including the importance of early clinical diagnosis, its etiology, possible associations with other pathologies, and different types of treatment.